Modelling pyro-convective activity in Pedrógão Grande mega fire - Couto, Flavio (2022)
The development of PyroCumulonimbus (PyroCb) clouds during mega fire events has high impact in the evolution of the fire fronts and have been observed more frequently in the last years. In 2017, Portugal was affected by several episodes of extreme wildfires with associated cloud systems. The present study aims to investigate the development of pyro-convective activity during the Pedrógão Grande episode. The study used the reference fire propagation deduced from the official investigation (forced fire) as well as reference boundary condition from atmospheric analysis to simulate the coupled simulation with a mesoscale atmospheric model at high temporal and spatial resolution. The MesoNH model has been configured into three nested domains with horizontal resolutions of 2000 m, 400 m and 80 m. The emission of heat and vapour into the atmosphere was made using the ForeFire model. The results highlight the importance of the use of cloud resolving models configured with very-high spatial and temporal resolutions for representing the development of phenomena associated to pyro-convective activity, namely those occurring in the microscale from the cloud microphysics processes, like very-localised microbursts.